Understanding the physiological effects of wearing enhanced personal protective equipment while providing patient care - Bulson, DNP, MPA, RN, NE-BC, Julie; Shawl, BBA, RRT, NHDP-BC, Kenneth (Journal of Emergency Management, 2019)
Purpose: There is a lack of information regarding the physiological effects of healthcare workers performing patient care while wearing enhanced personal protective equipment (PPE). This study aimed to provide foundational data necessary to maintain the health and safety of healthcare workers while performing tasks wearing enhanced PPE related to patient care in a biocontainment unit. Design and method: This study is a descriptive study evaluating the physiological effects of conducting patient care while wearing enhanced PPE. Participant vital signs (blood pressure, body temperature, and oxygen saturation) were monitored pre-donning, throughout the transport, and post-doffing. Results: There is no statistically significant difference in the physiological measurements of any of the participants. The results consisted of: blood pressure (systolic p = 0.0659; diastolic p = 0.94345); oxygen saturation (p = 0.6233); and orally derived body temperature (p = 0.1093). Physical balance was subjectively measured by both the participant and the trained observer during the donning and doffing process. Results show no visible difference in balance between the donning period and the doffing period. Conclusion: This study demonstrated there were no physiological changes to the healthcare workers in this study performing patient care activities during patient transport and in a biocontainment unit while wearing the provided enhanced PPE. However, limitations of this study include: (1) it was conducted at one location within the Midwest; (2) with a small number of participants; and (3) only the enhanced ensemble of PPE was worn during testing. Therefore, the results may not be generalizable to other locations or levels of PPE. Clinical relevance: This study will help to guide assessment standards for healthcare workers providing care while wearing enhanced level PPE.